Sensory, physicochemical, and functional stability of freeze-dried blackcurrant (Ribes nigrum L.) Snacks. Effect of sweeteners - Archaina, Diego (Food science and technology international = Ciencia y tecnologia de los alimentos internacional, 2024)
The objective of this work was to develop two freeze-dried snacks from blackcurrant and different sweeteners: honey/isomalt (HI) sweetened with honey/isomalt, and isomalt/stevia (IS) sweetened with isomalt/stevia. Both snacks showed high bioactive compounds retention (>75%) and no significant changes in several physicochemical properties after 6 months storage. Fresh snacks were hard and crunchy, and the perception of consumers within liking categories was: HI: 43%, and IS: 72%. After storage HI snack showed higher acceptance by consumers (75% within liking categories) while IS snack showed a decrease in their acceptance (63% within disliking categories). The penalty analysis showed that the sensory shelf-life of both snacks would be limited by the changes produced in texture and color during storage. HI snack could reach six storage months, while IS would be stored up to 3 months. The use of diverse sweeteners allowed obtaining two different products which could be incorporated into a healthy diet